Projecting a High-School Quarterback’s Performance at the Collegiate Level: A Comparison of the Rivals, 247 Sports, and ESPN Recruiting Ratings - Pitts, Joshua D; Poole, Stephen J; Stephens, Michael M (Journal of Amateur Sport, 2019)
We examine recruiting ratings for high-school quarterbacks over the period 2006-2012 from Rivals, 247 Sports, and ESPN. Using Lee & Preacher’s (2013) test of the difference between two dependent correlations with one variable in common and ordinary least squares regression, we determine that the Rivals ratings have the strongest correlation with quarterback performance over the time-period examined. The 247 Sports ratings follow closely behind the Rivals ratings; however, the ESPN ratings correlate more weakly with a quarterback’s career performance in college.